2012
DOI: 10.1039/c2cp42185b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition between DNA and a copper-based anticancer complex

Abstract: The aim of this work is to describe the specific recognition site between DNA and an anticancer copper complex by means of computational methods. Molecular dynamics were used to find the preferred site of binding between selected DNA chains and [Cu(2,2'-bipyridine)(acetylacetonate)(H(2)O)](+) (Cas). Full DFT optimizations of selected geometries extracted from simulations, followed by a topological analysis of electron density allowed us to define the specific interactions inside the recognition site. Cas links… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 55 publications
3
42
0
Order By: Relevance
“…Their Kb values are lower than that of the classical intercalator ethidium bromide (1.4 × 10 6 ) [35], and similar or higher than that of the Cu-phen complex ([Cu 2 (phen) 2 Cl 4 ], Kb of 4.75 × 10 4 M −1 [36]) and are in agreement with an interaction trough groove binding and partial intercalation, which may occur trough partial intercalation of phen moiety and of the phenyl ring of the Phe-containing dipeptides. A similar case of partial intercalation has been proposed recently for a related complex with bipy ([Cu(2,2′-bipyridine)(acetylacetonate)(H 2 O)] + ) by computational studies [37].…”
Section: Dna Binding Studiessupporting
confidence: 65%
“…Their Kb values are lower than that of the classical intercalator ethidium bromide (1.4 × 10 6 ) [35], and similar or higher than that of the Cu-phen complex ([Cu 2 (phen) 2 Cl 4 ], Kb of 4.75 × 10 4 M −1 [36]) and are in agreement with an interaction trough groove binding and partial intercalation, which may occur trough partial intercalation of phen moiety and of the phenyl ring of the Phe-containing dipeptides. A similar case of partial intercalation has been proposed recently for a related complex with bipy ([Cu(2,2′-bipyridine)(acetylacetonate)(H 2 O)] + ) by computational studies [37].…”
Section: Dna Binding Studiessupporting
confidence: 65%
“…Research indicated DNA-binding drugs exert their effects in an ion-dependent manner as the binding of metal ion complexes occur at specific sites on the DNA. For example, Mg2+ or Zn 2 + complexes preferentially bind to specific sites in DNA (20) .…”
Section: Cell Proliferation Vs Apoptosis and Simple Phenolic Compoundsmentioning
confidence: 99%
“…The DFT level of theory has previously been proven to adequately reproduce experimental structures. [19,20,40] For each complex a wavefunction file was obtained after a single point energy calculation at the same theoretical level. From these files, local and integrated properties were calculated by using the atomic definition of the Quantum Theory of Atoms in Molecules [41] in the AIM-ALL program.…”
Section: Computational Chemistrymentioning
confidence: 99%
“…The bond lengths, angles, and dihedral angles were calculated by using the parmcal program available in the AmberTools suit of programs and previously described. [19] To assess the interactions of the two copper compounds with a bilayer membrane, MD simulations were run with the compounds at two different starting positions (see Figure S1a,b in the Supporting Information). Each compound was manually positioned at either the surface of the membrane or inserted into the geometric center of mass (COM) of the entire membrane system.…”
Section: Computational Chemistrymentioning
confidence: 99%
See 1 more Smart Citation